Violence sexuelle ou « initiation » ? - Pierre Niedergang; Tal Piterbraut-Merx (Glad!)
Starting from the debates that have animated the French queer community around the legacy of Guy Hocquenghem, this article aims to deconstruct some binarisms (materialism/queer, feminism/queer, morality/anti-normativity) that constitute erroneous coordinates for thinking about the question of sexual violence against children and its treatment within queer communities. This reflection begins with a historical consideration of the origin of these tensions, which the authors situate in the debates on adult-child sexuality and its politicization in the 1980s in France. It continues with the observation of a difference in the treatment of the question of sexual violence within the lesbian and gay communities, and with an elaboration on the need to politicize the trauma. Finally, the article closes on the linkage between the question of trauma and the question of queer normativity which has been more and more explicitly important for the last ten years.